The Influence of Entrepreneurial Education on Entrepreneurial Capacity and Value Creation Development - Ubaid Ullah; Gul Ghutai; Muhammad Tariq (Indus Journal of Social Sciences, 2025)
The fundamental role of Higher Education Institution (HEIs) is the enhancement of entrepreneurial capacity and value creation in graduates to combat educational inflation and credentialism. This study aims to investigate how entrepreneurship education contributes to the improvement of entrepreneurial skills and stimulate value creation capacities among the students in HEIs, specifically in the context of Khyber Pakhtunkhwa, Pakistan. This study followed an inductive-qualitative research design to examine the perspectives and experiences of entrepreneurs, students, and educators in the context of entrepreneurship education in HEIs with help of thematic data analysis. This study identified many core themes such as development of an entrepreneurial mindset, value creation capacities development, and the importance of mentorship and institutional enablement and external support availability. The finding of this study indicates that interdisciplinary approaches, mentorship and experiential learning in promoting the entrepreneurial capacity are key drivers of entrepreneurial capacity and value creation development. This study revealed that challenges related to investing in resources, fostering supportive culture and bridging theory and practice dichotomies must be addressed by the HEIs to support entrepreneurial initiatives which will in turn prepare the students for entrepreneurship and value creation.